PENGARUH CITRA MEREK DAN KEWAJARAN HARGA TERHADAP LOYALITAS MEREK DENGAN KEPUASAN PELANGGAN SEBAGAI PEMEDIASI PADA PENGGUNA PRODUK APPLE DI KOTA BANDA ACEH - Indah Bestari, Nurdasila (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2017)
This research aims to know the influence of brand image and price fairness on brand loyalty with customers satisfaction as a mediator of Apple user in Banda Aceh. The sample used in this research are 170 respondents who are using iPhone  in two years modestly as well as knowing any of its feature. The sampling technique used here is Purposive sampling. Meanwhile, the tool for data analysis is SEM (Structural Equation Modeling) with variant based—Partial Least Square (PLS)—using SmartPLS 2.0 software. This research tells that the standard price is more dominant to affect the brand loyalty with the original sample number 0,239998. For increasing the standard price and giving the fair price to customers, fair and ethical price policy from the producer as well as price policy that is accepted and suitable for customers. Beside the standard price, brand image influence the brand loyalty with original sample number 0118234.  To adjust the brand image by giving the trusted, interesting, and great brand, the brand that can give a social symbol as well as good reputation. From this research, it is shown that brand image variable does not have any impact of brand loyalty through customers’ satisfaction as a mediator. Meanwhile, the standard price variable gives an impact to brand loyalty through customers’ satisfaction as a mediator. Keywords : Brand Image, Standard Price, Brand Loyalty, Customers   Satisfaction.